Depression, anxiety and associated factors among Chinese adolescents during the COVID-19 outbreak: a comparison of two cross-sectional studies - Chen, Xu; Qi, Han; Liu, Rui; Feng, Yuan; Li, Wen; Xiang, Mi; Cheung, Teris; Jackson, Todd; Wang, Gang; Xiang, Yu-Tao (Translational psychiatry, 2021)
The 2019 coronavirus disease (COVID-19) is a public health emergency of international concern. In China, all schools were shut down and students were home quarantined to prevent disease spread; these steps could have potential negative effects on mental health of adolescents. This study aimed to examine changes in depression and anxiety among Chinese adolescents during the COVID-19 epidemic, and explore factors associated with depression and anxiety. Two survey administrations were conducted among Chinese adolescents between February 20 and February 27 and between April 11 and April 19, 2020, respectively. The Center for Epidemiological Studies-Depression Scale (CES-D) and the 7-item Generalized Anxiety Disorder (GAD-7) scale were used to assess depressive symptoms and anxiety symptoms, respectively. A total of 9554 and 3886 adolescents participated in the first and second surveys. During the initial survey, the prevalence of depression was 36.6% (95% CI: 35.6–37.6%) while the prevalence of anxiety was 19% (95% CI: 18.2–19.8%). Rates of depression and anxiety increased to 57.0% (95% CI: 55.4–58.6%) and 36.7% (95% CI: 35.2–38.2%), respectively, in the second survey. Multivariable logistic regression analyses revealed that group membership in the second survey, female gender, senior secondary school enrollment, and concerns about entering a higher grade were positively associated with both depression and anxiety. Conversely, a sleep duration of ≥6 h/day, an exercise duration ≥30 min/day, having the same as typical or higher study efficiency during the COVID-19 outbreak, and living in provinces with 1000–9999 confirmed COVID-19 cases were negatively associated with depression and anxiety. In conclusion, compared to figures reported during the COVID-19 outbreak, the prevalence of depression and anxiety in Chinese adolescents significantly increased after the initial outbreak. Regular screening and appropriate interventions are urgently needed to reduce the risk for emotional disturbances among adolescents during and after the initial COVID-19 outbreaks.